Role of Ni and Zn Dopants in Modulating the Structure and Photocatalytic Activity of Mesoporous Silica–Cu Catalysts for Methylene Blue Degradation - Maria Ulfa; Suwiji Lestari (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
This study investigates the structural and photocatalytic roles of Ni and Zn dopants in mesoporous silica–Cu catalysts for methylene blue degradation under light irradiation. The materials were synthesized and systematically characterized using FTIR, XRD, BET, SEM–EDS, and UV–DRS to elucidate dopant-dependent structural, textural, and electronic modifications. XRD analysis revealed that Zn doping enhances crystallinity to 90.80% with a crystallite size of 1.97 nm, whereas Ni doping produces lower crystallinity (80.69%) and smaller crystallites (1.82 nm), indicating defect-rich microstructures. BET analysis confirmed mesoporous characteristics in both systems, with Zn incorporation generating broader pore distributions and higher adsorption capacity, while Ni induces more confined pore structures. SEM results showed average particle sizes of 1.49 nm for Zn-doped and 1.67 nm for Ni-doped catalysts. UV–DRS measurements demonstrated pronounced electronic modulation, with Ni doping significantly narrowing the band gap to 1.02–1.11 eV compared with 2.08–2.78 eV for Zn-doped materials. Photocatalytic evaluation at an initial methylene blue concentration of 5 ppm showed superior performance for the Ni-doped catalyst, achieving 79.59% removal efficiency and an adsorption capacity of 19.89 mg.g⁻¹, compared with 50.98% removal and 12.74 mg.g⁻¹ for the Zn-doped system. Kinetic analysis followed pseudo-first-order behavior, with a higher rate constant for Ni doping (0.01675 min⁻¹) than Zn doping (0.00706 min⁻¹). These findings demonstrate that Ni primarily enhances photocatalytic activity through electronic defect formation and band gap narrowing, while Zn mainly improves structural ordering and pore accessibility. The study highlights the critical role of dopant selection in tailoring structure–activity relationships in mesoporous silica–Cu photocatalysts. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).